Frequency Domain Diagnostics of Transformer Insulation - M. Gutten; M. Šebok; D. Korenčiak; P. Brnčal; M. Kubiš; P. Żukowski; T. N. Koltunowicz (Приборы и методы измерений)
The first part of paper deals with the base information about diagnostics of power transformers. In this part are presented differently insulating methods, for example method of recovery voltage method, method of polarization and depolarization currents and chromatographic analysis.The second part of paper deals use of method of frequency domain spectroscopy for oil power transformers. This method is used in analysis insulating condition of power transformer with system of oil-paper. It was found, that the results of these tests are highly impacted by the operating temperature during the experimental measurement. Moisture and conductivity between insulating paper and oil in an insulating system are highly dependent from temperature.In the other part, the paper presents experimental results of the frequency diagnostic measurement for a real single-phase traction transformer 110/27 kV at different operating temperatures and states (with oil and without).Finally in the last part, the paper presents comparing frequency insulating measurements among several the same single-phase transformers 110/27 kV.